Building Religious Harmony and Tolerance: Social Da’wa by Sayyid Ahmad bin Salim Al Muhdlor - Ahmad Nurcholis; Moh. Arif; Heri Efendi; Wiwik Sunarsih (Universitas Islam Negeri Mataram, 2021)
Most activities of Islamic propagation (da’wah) focus on a conventional method of normative teaching that may result in fanaticism and dogmatism. However, da’wah activity should be also inclusive and attentive to the context where it is held. The purpose of this article is to describe, analyze, and interpret the social da’wah carried out by Sayid Ahmad that could create religious harmony and tolerance in Tulungagung, East Java. Based on the theory of structural functionalism by Talcott Parsons, this phenomenological study analyses the structure of society and the interrelationships of various structures seen to be mutually supportive of dynamic equilibrium. This theory focuses on how good order is maintained among various elements of society. This study shows Sayyid Ahmad uses social da’wah approach by establishing economic harmonization, building educational institutions to teach tolerance values, constructing mosques by different religious adherents to realize the meaning of tolerance, and completing the mosque with good facilities and infrastructure. He also teaches the pillars of tolerance and harmony among religious communities by serving and helping each other, giving justice to anyone, and respecting other religions.